Development Trends Of Real Estate Taxation In Uzbekistan (Eurasian Journal of Humanities and Social Sciences, 2025)
This article provides information on the development of a methodology for assessing real estate objects for the introduction of real estate tax, the creation of a unified cadastre of real estate objects, as well as work related to the reform of land legislation and problems in creating a cadastre of real estate objects, as well as the complexity of real estate valuation, which leads to delays in the introduction of this tax